Possible Role of Interleukins 6 and 10 in Colorectal Carcinoma in Iraqi Patients - Mousawy, Khalida M. (Journal of the Faculty of Medicine Baghdad, 2005)
Background : It is quite accepted that interleukins (IL) in general play a crucial role in response to injuy , infection and on cogenic trans formation , among there are IL-6 and ILJO. Aim of this study is to find out the possible role of IL_ and IL, 10 in colo rectaI carcima in Iraqi patients. Subjects and Methods: forty patients with colorectal cancer (CRC) composed with 30 healthy controls were enrolled in this study. Serum conc. Of IL-6 and IL -lOwere estimated in both groups using ELIZA technique. Results: Serem levels of IL-6 and IL-10 were significantly increased (P<0.001) in compassion with control group. Conclusion: these cytokins could be used as a markers for tumor progression .